Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPS Madrasah Ibtidaiyah melalui Metode Gallery Walk - Nurpadilah, Ai; Darifah, Udung Hari; Dudi, Dudi (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
This study is based on the low learning outcomes of students on IPS subjects. As it is known that the Education Unit Level Curriculum (KTSP) demands complete learning according to the conditions of students and schools, so that in SD Negeri 4 Banjarharja has been set Minimum Exhaustiveness Criteria (KKM) for Social Science subjects (IPS) class V of 75. However The circumstances that occur in the field is the result of learning IPS obtained by V grade students about 40% or 12 students still get the value below the KKM with an average value of 72.25. Therefore, as an effort to improve learners' learning outcomes, researchers apply learning method gallery walk. The method used in classroom action research (PTK) research model Kurt Lewin. Data collection techniques are observation techniques, test and assessment techniques, and descriptive analysis techniques. After doing research, learning result of learners with the use of gallery walk learning method has increased, that is pre cycle average 72,25 with completeness percentage reach 40%, in cycle I reaching average value 79 with percentage mastery reach 65%, while in the second cycle reached an average value of 83.25 with a percentage of completeness reached 80%, and in the third cycle reached an average value of 89.75 with a percentage of completeness reached 100%. Thus, the learning method gallery walk can improve learning outcomes of learners.